Protection of mice from fatal Toxoplasma gondii infection by immunization with p30 antigen in liposomes. - Roland Bülow; John C. Boothroyd (1991)
Using liposomes as adjuvant, a purified membrane Ag from Toxoplasma gondii (p30) has been tested for its protective effect in mice. Immunization with p30 in liposomes resulted in only one in 15 mice dying from a challenge that killed 11 of 15 control mice (receiving only buffer or liposomes without p30). The p30 Ag alone gave intermediate levels of protection, with 5 of 15 animals dying. The source of the p30 Ag was the rapidly growing, laboratory-adapted strain of T. gondii, RH; challenge was with the recently isolated C strain which still has all the properties of a wild-type strain. To assess the validity of this combination, the amino acid sequence of p30 from these two strains (as predicted from the corresponding gene sequence) was compared and found to differ in only eight residues. This minimal variation argued that RH was a valid source of material for a subunit vaccine, as subsequently confirmed by the protection studies. These results indicate that p30 is an appropriate Ag for development into a subunit vaccine for immunization of humans and/or domestic livestock, which are a major source of human infection.